CUSTOMS CLEARANCE PROCESS DISCOVERY OF RED LANE IMPORT GOODS - Sulistyarini, Galuh Dwi; Luluk Fauziah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the customs clearance process for the discovery of imported goods in the red lane. Method: This research used a qualitative method with data collection through interviews, observations, and documentation. Results: The results of the study indicate that the customs clearance process for the discovery of imported goods in the red lane is quite complex, which includes an in-depth examination of documents and physical imported goods, verification of the status of the found goods if they are classified as Non-LARTAS must payment SPTNP, while goods included in the LARTAS category then the goods are not allowed to leave by Customs so that the Release of Part of the Imported Goods applies after the issuance of SPPB Notes. Novelty: Customs Clearance is a crucial process in international trade activities, especially imports. This process involves a channeling response from Customs, one of them is the red lane. Where imported goods require further action due to certain risk factors.